Atomic layer deposition of ZnO layers on Bi2Te3 powders: Comparison of gas fluidization and rotary reactors. Issue 24 (15th December 2022) - Jung, Myeong Jun; Ji, Myeongjun; Han, Jeong Hwan; Lee, Young-In; Oh, Sung-Tag; Lee, Min Hwan; Choi, Byung Joon
Abstract: Interface engineering of thermoelectric powder materials via atomic layer deposition (ALD) has attracted significant research interest owing to the dramatic improvement in energy conversion efficiency. Using ALD to uniformly coat ultrathin (a few nanometers) ZnO layers on the microscale irregular shape of bismuth telluride-based powders is a challenge. An ALD reactor that fluidizes or agitates the powders can be adapted for this purpose. In this study, two types of ALD reactors, a gas fluidization reactor and a rotary reactor, were used to coat selenium-doped bismuth telluride powders with ZnO. Uniform and conformal ZnO layers were successfully grown using both the ALD reactors. However, the crystalline structure, particle size distribution, and chemical bonding states of ZnO were affected by reactor type. Pelletization of the ALD-coated powders was performed by spark plasma sintering at a high temperature (500 °C) and pressure (60 MPa). The morphologies of the powders did not change with palletization; however, differences in the chemical states of the ZnO layers on the BTS powders were observed. It was observed that the remnant water molecules and mobile ion species might compensate for the carrier mobility in pellets made of ALD-coated powders. Graphical abstract: Image 1